Tenecteplase vs. alteplase for treatment of acute ischemic stroke: A systematic review and meta-analysis of randomized trials - Kobeissi, Hassan; Ghozy, Sherief; Turfe, Bilal; Bilgin, Cem; Kadirvel, Ramanathan; Kallmes, David F.; Brinjikji, Waleed; Rabinstein, Alejandro A. (Frontiers in Neurology, 2023)
Background and objectives Several randomized controlled trials (RCTs) have compared tenecteplase to alteplase for treatment of acute ischemic stroke (AIS). Yet, there is no meta-analysis that includes the latest published RCTs of 2022. We sought to compare the safety and efficacy of tenecteplase vs. alteplase for the treatment of AIS through a meta-analysis of all published RCTs. Methods A systematic literature review of the English language literature was conducted using PubMed, Web of Science, Scopus, and Embase. We included RCTs that focused on patients with AIS treated with tenecteplase and alteplase. Multiple reviewers screened through potential studies to identify the final papers included in our analysis. Following PRISMA guidelines, multiple authors extracted data to ensure accuracy. Data were pooled using a random-effects model. Results Nine trials, with 3,706 patients, compared outcomes of patients treated with tenecteplase and alteplase for AIS. Both treatments resulted in comparable rates of modified Rankin Scale (mRS) 0–1 at 90 days (RR = 1.03; 95% CI = 0.97–1.10; P-value = 0.359) and mRS 0–2 at 90 days (RR = 1.03; 95% CI = 0.87–1.22; P-value = 0.749). There was no heterogeneity among included studies regarding mRS 0–1 rates (I2 = 26%; P-value = 0.211); however, there was significant heterogeneity in mRS 0–2 rates (I2 = 71%; P-value = 0.002). Similarly, rates of mortality (RR = 0.97; 95% CI = 0.81–1.16; P-value = 0.746) and symptomatic intracranial hemorrhage (sICH) rates (RR = 1.10; 95% CI = 0.75–1.61; P-value = 0.622) were comparable in both treatment groups. There was no significant heterogeneity among included studies in either mortality (I2 = 30%; P-value = 0.181) or sICH (I2 = 0%; P-value = 0.734) rates. Further analysis comparing dosing of tenecteplase (0.1, 0.25, 0.32, and 0.4 mg/kg) yielded no significant differences for any of the endpoints (mRS 0–1, mRS 0–2, sICH, and mortality) compared to alteplase. Discussion Based on available evidence from completed RCTs, tenecteplase has proven similar safety and efficacy to alteplase for treatment of AIS.